Accumulation of Cd, Cu, Cr, and Pb in Whiteleg Shrimp and Pond Environment of Traditional Aquaculture Systems in Sidoarjo, Indonesia - Sugiarto, Kevin Pratama; Kilawati, Yuni; Mahmudi, Mohammad (Universitas Gadjah Mada, 2025)
This study investigates the accumulation of heavy metals cadmium (Cd), copper (Cu), chromium (Cr), and lead (Pb) in the water, sediment, and body parts of whiteleg shrimp (Litopenaeus vannamei) cultured in traditional aquaculture ponds in Sidoarjo, Indonesia. The ICP-AES method showed that heavy metals were more concentrated in sediment than in water, particularly Pb and Cd. Cd levels in water and Pb levels in sediment exceeded national and international quality standards. In shrimp tissue, the highest accumulation occurred in the cephalothorax, especially for Cu, although all detected levels remained within the safety limits set by Indonesian standards. Monitoring heavy metals in the aquaculture environment and shrimp is essential, as these contaminants can bioaccumulate and pose health risks to aquatic organisms and humans throughout the food chain. Water quality parameters were generally suitable for shrimp farming, but low pH values may increase heavy metal solubility and bioaccumulation risks. These findings highlight the need for regular monitoring and better environmental management to ensure the sustainability and safety of traditional shrimp aquaculture systems.